2009
DOI: 10.1001/archpediatrics.2009.75
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Fetal Disproportion and Birth Asphyxia in Rural Sarlahi, Nepal

Abstract: Participants: Mothers and newborns (n = 3189). Outcome Measure: Birth asphyxia, defined as an infant who failed to cry at birth, and who was unable to breathe or suckle normally after birth or had convulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Although our data collectors were highly trained and used standardized questionnaires to elicit morbidity histories every 24 hours, our data may suffer from reporting bias and misclassification. Yet, we used previously validated algorithms for defining sepsis and birth asphyxia [21,23,27]. The other consideration is that hospital-based, physician diagnosed conditions may be very likely to identify severe morbidity, and emergency interventions may have resulted in improved survival, whereas our self-reported morbidity symptoms among surviving neonates were likely less severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data collectors were highly trained and used standardized questionnaires to elicit morbidity histories every 24 hours, our data may suffer from reporting bias and misclassification. Yet, we used previously validated algorithms for defining sepsis and birth asphyxia [21,23,27]. The other consideration is that hospital-based, physician diagnosed conditions may be very likely to identify severe morbidity, and emergency interventions may have resulted in improved survival, whereas our self-reported morbidity symptoms among surviving neonates were likely less severe.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was defined as at least 2 consecutive days of 2 of the following symptoms: 1) inability or difficulty suckling, 2) lethargy, 3) difficulty breathing, 4) convulsions or stiffness of back, 5) hot to touch or temp > 100°F, 6) cold to touch or temp < 96.6°F, 7) red purulent umbilicus [21]. Birth asphyxia was defined as inability to cry at birth and one of the following symptoms: 1) inability to breathe at birth, 2) convulsions or spasms, or 3) inability to suckle normally after birth [23]. Data were analyzed with all maternal and child intervention groups combined for two reasons - one, combinations of micronutrients in the maternal supplementation trial was shown to impact some of the exposure variables in this analysis and was deemed as being in the causal pathway [11,21] and two, child supplementation with iron-folic acid and/or zinc had no impact on the outcomes [9].…”
Section: Methodsmentioning
confidence: 99%
“…These results are generally consistent with a UNIMAPP trials analysis [43] with a notable, though non-significant increase in early neonatal mortality (OR = 1.23; 95% CI: 0.96 – 1.59), while there was a 6% non-significant reduction in late neonatal mortality (OR = 0.94; 95% CI: 0.73 – 1.23). These findings suggest that the use of multiple micronutrient supplements in populations to address maternal anemia and reduce the incidence of SGA, must be accompanied by the provision of skilled care at delivery and facility births to offset any potential increase in the risk of obstructed labour and birth asphyxia [44,45]. It must be noted that in most studies evaluated, despite reduction in rates of SGA, there was no reduction in neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Programs to reduce intrapartumrelated injury must address risk factors across the entire continuum of the life cycle from adolescence through pregnancy and childbirth. For example, ensuring adequate child nutrition may reduce rates of maternal stunting, and delayed age of first birth may decrease the risk of obstructed labor [80]. Interventions for the primary prevention of intrapartum-related injury are required during the time of pregnancy and childbirth, while secondary and tertiary prevention measures are needed in the immediate postnatal and neonatal periods.…”
Section: Addressing Deadly Delays: the Need For Linkagesmentioning
confidence: 99%